2016
DOI: 10.1186/s12911-016-0348-6
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of method for defining conditions using Chinese electronic medical record

Abstract: BackgroundThe adoption of the electronic medical record (EMR) is rapidly growing in China. Constantly evolving, Chinese EMRs contain vast amounts of clinical and financial data, providing tremendous potential for research and policy use; however, they are only partially standardized and contain free text or unstructured data. To utilize the information contained in Chinese EMRs, the development of data extraction methodology is urgently needed. The purpose of this study is to develop and validate methods to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Liver disease variables were defined using our previously developed and validated EMR case definitions [30]. The validation study showed that most of the case definitions had high validity (positive predictive value over 80%).…”
Section: Methodsmentioning
confidence: 99%
“…Liver disease variables were defined using our previously developed and validated EMR case definitions [30]. The validation study showed that most of the case definitions had high validity (positive predictive value over 80%).…”
Section: Methodsmentioning
confidence: 99%
“…The mission of health care institutions – restoring patient’s health – demands effective and efficient medical data for evidence-based intervention 1. Installing an appropriate health care data management system with valid case definition enables efficient data extraction,2 improves communication for clinical decision making in medical practice,28 and clinical research,9,10 and upgrades the quality of health care services 11. Healthcare professionals are responsive to improve recording, distributing, monitoring, and implementing preventive measures to decrease morbidity 12.…”
Section: Introductionmentioning
confidence: 99%
“…Patient data were readily accessible and transferable21 from the EHR system. This helps to make an accurate diagnosis and decision making22 by reducing the access time and use 1,2. Notification signal flags or BPAs prompt about “what content” and “with whom” to share2325 that trigger potential adverse events (AEs) using easily identifiable displays that alert patient records reviewers 26.…”
Section: Introductionmentioning
confidence: 99%
“…We had no access to any patient identifying information as part of the study. In our previous study, we developed and validated a data extraction method for a Chinese EMR, and we defined 40 liver disease severity and comorbidity variables using this extraction method [ 35 ].…”
Section: Methodsmentioning
confidence: 99%